Surgical treatment of anterior cervical osteophytes causing dysphagia. (25th March 2019) - Ruetten, Sebastian; Baraliakos, Xenophon; Godolias, Georgios; Komp, Martin
Purpose: Dysphagia due to anterior cervical osteophytes is a rare condition. However, it can become serious enough to permanently impair the quality of life up to making normal food intake impossible. If conservative treatment fails, there is the option of surgical resection of the osteophytes. The objective of this study was to assess the outcomes of resections of anterior cervical osteophytes causing spondylogenic dysphagia, taking literature into consideration. Method: Resection of anterior cervical osteophytes using a standard anterior approach was performed in 14 consecutive patients with spondylogenic dysphagia between 2009 and 2015. Indomethacin or radiation was used to prevent recurrence. Imaging and clinical data were collected in follow-up examinations over an average of 50 months. Results: The osteophytes were sufficiently resected in all cases. Anterior plates were placed in three patients due to pronounced segmental mobility. Five patients were given recurrence prevention in the form of indomethacin, nine with radiation. One patient required revision surgery for a hematoma. No other serious complications were observed. All patients had significant improvement of their symptoms. No recurrences or signs of increasing instability were found during the follow-up period. Conclusion: When conservative treatment fails, surgical resection of cervical osteophytes is a sufficient method for treating spondylogenic dysphagia. High patient satisfaction and improvement of the quality of life are achieved with a low complication rate. Routine additional stabilization has been discussed as recurrence prevention. Prophylaxis using indomethacin or radiation, known primarily from hip replacement, also appears to be an option.